Volumetric data throughput optimisation by dynamic FEC bearing frame length adaptation - Christelis, Christian (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.